Adaptive Fuzzy Modal Matching of Capacitive Micromachined Gyro Electrostatic Controlling - Li Cheng; Ruimin Liu; Shumin Guo; Gaofeng Zheng; Yifang Liu (Sensors, 2023)
A fuzzy PI controller was utilized to realize the modal matching between a driving and detecting model. A simulation model was built to study electrostatic decoupling controlling technology. The simulation results show that the modal matching can be gained by the fuzzy PI controller. The frequency difference between the driving mode and the detection mode is less than 1 Hz, and the offset of the input DC is smaller than 0.6 V. The optimal proportionality factor and integral coefficient are 1.5 and 20, respectively. The fuzzy PI controlling technology provides a good way for the parameter optimization to gain modal matching of micro gyro, via which the detecting accuracy and stability can be improved greatly.